PENGETAHUAN AKAN ALLAH: ANTARA IMPOSSIBILITAS DAN SURPASSIBILITAS - Oktovianus Naif (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2020)
Man and woman are created in God’s image so they have desire to know their Creator and they also need God in their lives which causes the desire to know Him. The desire in question, then, is a desire to understand God. For the desire is prior to knowing and it is compatible with not knowing. It is true if we say that man’s unrestricted desire to know is mated to a limited capacity to attain knowledge about Him.For its finiteness human capabilitycould not get hold of a complete knowledge of God.In knowing God and aknowledging Him as Being of beings, human beings must be aware of his ignorance that is “the only true wisdom is in knowing I know nothing.” God, therefore, takes the first step to contact with human beings, then He reveals Himself, He gives Himself to be known and He makes Himself known by human beings. This is a self-manifestation of Someone to someone. Revelation is due to the intiative of God that is God reveals Himself, when He wills, to whom He wills and because He wills. God’s revelation illuminates the intellectual capabilityof humans so that human beings are able to know Him and aknowledge Him and talk about Him as Being of beings. Knowledge of God is called theology. Ultimately, theology is about God in Himself. Thus, theology is the peak of knowledge and the fullness of gnosis since it was brought about under the guidance of the Spirit.So, we could say, God makes knowledge possible for human beings and God is really the Possibler of knowledge and aknowledge of Himself.